1975
DOI: 10.2527/jas1975.40129x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Heterosis in Swine: Reproductive Performance and Dam Productivity

Abstract: SummaryThe objectives of this study were to estimate the heterosis of crossbred gilts for ovulation rate and the maternal heterosis of crossbred gilts for dam productivity. A total of 470 gilts were saved for breeding of which 72 were considered reproductive failures. Estimates of heterosis were made from 193 pregnant gilts slaughtered 30 days postbreeding (106 crossbred and 87 purebred)and 192 litters farrowed (98 three-breed and 94 two-breed cross).The reproductive failure rate for all gilts was 15.3% with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 5 publications
2
6
0
Order By: Relevance
“…Estimates presented in table 23 were 3.2 (P<.01), 3.2 (P<.01), 13.0 (P<.01), 29 (P<.05) and 77 pounds for litter weight born, born alive and at 21, 56 and 154 days, respectively. These estimates agreed with those of Johnson and Omtvedt (1975) but are somewhat higher than those of Smith and King (1964). Deviations witliin a group with a common letter do not differ significantly (P<.05).…”
Section: **(?supporting
confidence: 74%
See 2 more Smart Citations
“…Estimates presented in table 23 were 3.2 (P<.01), 3.2 (P<.01), 13.0 (P<.01), 29 (P<.05) and 77 pounds for litter weight born, born alive and at 21, 56 and 154 days, respectively. These estimates agreed with those of Johnson and Omtvedt (1975) but are somewhat higher than those of Smith and King (1964). Deviations witliin a group with a common letter do not differ significantly (P<.05).…”
Section: **(?supporting
confidence: 74%
“…(Johnson and Omtvedt, 1975;Johnson et al, 1974) has indicated that maternal heterosis was of little importance for similar traits.…”
Section: 0mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, JOHNSON et al (1978) reported that crossbred gilts weaned 1.24 more pigs than purebred gilts. Also, JOHNSON and OMTVEDT (1975) found that crossbred gilts consistently had larger litters at all ages. Increases in number weaned of 5,10 to 19, and 20% were reported for crossbred sows by SMITH and KING (1964), MCLAREN and SMITH (1972) and DILLARD and ROBISON (1968), respectively.…”
Section: Resultsmentioning
confidence: 88%
“…These estimates agreed with those of Willham (1950), Smith and McLaren (1967), and Bereskin e^ al. (1974) but are somewhat higher than those of Young e^ (1976aYoung e^ ( , 1976b (Johnson and Omtvedt, 1975;Johnson et al, 1974) has indicated that maternal heterosis was of little importance for similar traits.…”
Section: Methodsmentioning
confidence: 92%